2022 American Society of Anesthesiologists Practice Guidelines for Management of the Difficult Airway*. (11th November 2021) - Apfelbaum, Jeffrey L.; Hagberg, Carin A.; Connis, Richard T.; Abdelmalak, Basem B.; Agarkar, Madhulika; Dutton, Richard P.; Fiadjoe, John E.; Greif, Robert; Klock, P. Allan; Mercier, David; Myatra, Sheila N.; O'Sullivan, Ellen P.; et al.
Abstract : The American Society of Anesthesiologists; All India Difficult Airway Association; European Airway Management Society; European Society of Anaesthesiology and Intensive Care; Italian Society of Anesthesiology, Analgesia, Resuscitation and Intensive Care; Learning, Teaching and Investigation Difficult Airway Group; Society for Airway Management; Society for Ambulatory Anesthesia; Society for Head and Neck Anesthesia; Society for Pediatric Anesthesia; Society of Critical Care Anesthesiologists; and the Trauma Anesthesiology Society present an updated report of the Practice Guidelines for Management of the Difficult Airway. Abstract : These practice guidelines update the "Practice guidelines for management of the difficult airway: A report by the American Society of Anesthesiologists Task Force on Management of the Difficult Airway." These updated guidelines are intended for use by anesthesiologists and all other individuals who deliver or who are responsible for difficult airway management. The update may also serve as a resource for other physicians and healthcare professionals who manage patients with expected, unexpected, or emergency difficult airways. Supplemental Digital Content is available in the text.